Prevalencia de Toxoplasmosis en Caninos Domesticos (canis familiaris) en el Barrio La Laguna - Pérez Ortiz, Ángel Patricio (2018)
Toxoplasmosis is a worldwide disease that affects human and animal health, so this research will focus on collecting blood samples from dogs in the La Laguna neighborhood, to verify the prevalence of toxoplasmosis and thus have specific data on the disease, in dogs of the province of Cotopaxi, which will allow education and information on toxoplasmosis taking into account the current situation, on public and animal health, would also be provided to people who have a dog as a pet or as a guardian, who Obtain knowledge of toxoplasmosis prevention in your dogs and in the future through projects generated for compliance with the regulations, which are currently handled in terms of dog care, in order to have healthy and healthy pets without worrying that they may have and transmit diseases.